eCM 2011
DOI: 10.22203/ecm.v022a05
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastin is not implicated in bone remodelling and repair

Abstract: Ameloblastin (AMBN) is an enamel matrix protein produced by ameloblasts. It has been suggested that AMBN might also be implicated in craniofacial bone formation. Our objective was to determine whether AMBN has an effect on osteogenic mineralisation and infl uences bone remodelling and repair. MC3T3-E1 cells were screened for endogenous expression of enamel proteins using real time PCR. Various osteogenic cells were infected with lentivirus encoding for AMBN and protein expression was verifi ed using immunochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
2
1
2
Order By: Relevance
“…AMBN might have three functions in this process, (i) to provide additional templating sites for bone mineralization, (ii) to enhance cell adhesion as a requirement for mineralized tissue formation, and (iii) to modulate osteogenic signaling via BMPs, Runx2 and Osx. Differences between our findings indicating that loss of AMBN function results in delayed bone fracture healing and a previous report (39) are likely due to differences in data interpretation and analysis techniques.…”
Section: Discussioncontrasting
confidence: 98%
“…AMBN might have three functions in this process, (i) to provide additional templating sites for bone mineralization, (ii) to enhance cell adhesion as a requirement for mineralized tissue formation, and (iii) to modulate osteogenic signaling via BMPs, Runx2 and Osx. Differences between our findings indicating that loss of AMBN function results in delayed bone fracture healing and a previous report (39) are likely due to differences in data interpretation and analysis techniques.…”
Section: Discussioncontrasting
confidence: 98%
“…5). Indeed, distinct dysmorphologies characterize bones in which AMELX [16], [49] or AMBN [24], [50] expression are genetically modified, even though calcium and phosphorus content and the degree of mineralization are normal [51], [52]. Disturbed EMP expression patterns are associated with alveolar and jaw bone malformations [33], [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that (i) AMBN expression was reported during craniofacial bone development in rats [ 35 ], and (ii) in vitro and in vivo experiments have suggested that this protein could also play a role in bone formation and repair [ 27 , 36 , 37 ]. These findings could indicate that AMBN plays a role in early bone formation and modeling, but they have been contradicted by a study showing no implication in bone modeling and repair [ 38 ]. Moreover, a possible function in bone development remains elusive as (i) AMBN −/− mice do not exhibit apparent bone phenotype [ 21 ], (ii) AMBN is subjected to pseudogenization in birds and in mammalian species, in which the capability to form either enamel or teeth has been lost, e.g., xenarthrans, pangolins and baleen whales, indicating that AMBN is a tooth specific protein [ 39 41 ], and (iii) AMBN expression was found to be restricted to teeth in rodents and in a crocodile [ 9 , 14 ].…”
Section: Introductionmentioning
confidence: 95%